Parental Reactions to Children’s Negative Emotions in France and the United States: Links to Preschoolers’ Socioemotional Outcomes - Kathryn Li; Claire Hofer; Aya I. Williams; Qing Zhou (Social Sciences)
Parental reactions to children’s negative emotions (PRCNEs), a type of emotion socialization, has been theorized to shape children’s socioemotional development. Few studies have examined cultural variations in PRCNE among Western/Minority World cultures. The present study used a cross-cultural, preschool-based sample of 101 parent–child dyads (child age = 36–79 months, 42% females; parent age = 19–58 years, 89% mothers) from two countries: U.S. (n = 33, 58% White/European American, 87% with college or above education) and France (n = 68, 61% French or other European origin, 40% with college or above education). Parents self-reported PRCNEs across 12 hypothetical scenarios. Children’s behavioral problems and prosocial behaviors were rated by parents and preschool teachers. Children’s emotion knowledge was measured by a behavioral task. We examined (1) cultural group variations in PRCNEs, and (2) the relations between PRCNE and children’s socioemotional outcomes. Controlling for demographics, French parents endorsed more non-supportive PRCNE than U.S. parents. Across both cultures, parents’ higher use of distress and punitive reactions were linked to lower parent-rated child prosocial behaviors. These findings revealed differences and similarities in PRCNEs between French and U.S. families and have implications for early childhood education practices promoting socioemotional competence.